No time for goodbye - Barclay, Linwood (Bantam Books, 2007)
Fourteen-year-old Cynthia Bigge wakes up one morning to find her entire family gone. Twenty-five years later, their unexplained disappearance still haunts her. She agrees to appear on the reenactment show Deadline, hoping the TV exposure might provide her with some answers, although her husband, English teacher Terry Archer, is considerably more skeptical. Indeed, not long after the show airs, the two are shaken down by a psychic, receive a series of bizarre phone calls, and become the victims of a break-in, although nothing is taken; instead, something is left--a hat that Cynthia is convinced belonged to her father.